Exploring Students' Online Learning Interaction Behaviors and Experiences : A Case Study - Chwen Jen, Chen; Chee Siong, Teh (International Society for the Scholarship of Teaching and Learning (ISSOTL), 2022)
This study chose an undergraduate course offered at a public university in Malaysia as the case to discover students’ unseen online interaction behaviors and experiences in order to obtain insights into ways to devise relevant online pedagogical approaches. The study employed the learning management system’s (LMS) analytics and the analysis of interactions within the social messaging app and virtual live classes to discover students’ online interaction behaviors, focusing mainly on student-content, student-instructor interactions, and student-student interactions. It also employed interviews and a survey to gain insights into students’ online learning experiences. The analysis and reflection of the derived online interaction behaviors and experiences reveal that students require conducive learning environments, regular check-ins on their progress and social-emotional well-being, and favor the learning flexibility afforded by asynchronous learning. It also provides insights into commendable pedagogical practices and reveals some considerations in virtual communication and virtual collaboration to improve students’ online interaction behaviors and experiences.